THE FEATURES OF TEACHING ENGLISH IN HIGHER EDUCATION SYSTEM (Academia Science Repository, 2023)
The article is focused on the features of teaching English in higher schools. As it is emphasized the need to improve students’ speaking, writing, reading and listening skills from English classes. It also outlines integrative and communicative approaches and goals that can be used to enhance the effectiveness of the lesson.